2020
DOI: 10.1002/ppap.202000052
|View full text |Cite
|
Sign up to set email alerts
|

Microbial decontamination of chicken using atmospheric plasma bubbles

Abstract: In this study, we demonstrate that atmospheric air plasma bubbles are an effective, energy‐efficient, residue‐free alternative to current decontamination techniques. Five to fifteen minutes of plasma‐bubble treatments of inoculated chicken skin led to a significant reduction in colony‐forming units (CFUs). We show that the activation efficiency is dependent on the plasma discharge frequency, with a higher one (2,000 Hz) leading to a higher CFU reduction (1.4 log) as compared with a lower (0.3 log) reduction at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…It was recently shown that an increase in discharge frequency led to a higher amount of key reactive species, including hydrogen peroxide, nitrite, nitrate and ozone. This, in turn, led to a higher reduction in viable bacterial cells 37 . Generally, the design of a PAW reactor will influence the production of specific ROS or RNS.…”
Section: How To Generate Paw and Regulate The Aqueous Ronsmentioning
confidence: 97%
“…It was recently shown that an increase in discharge frequency led to a higher amount of key reactive species, including hydrogen peroxide, nitrite, nitrate and ozone. This, in turn, led to a higher reduction in viable bacterial cells 37 . Generally, the design of a PAW reactor will influence the production of specific ROS or RNS.…”
Section: How To Generate Paw and Regulate The Aqueous Ronsmentioning
confidence: 97%
“…The cathode sheath is important for plasma processing, and we chose nitrogen discharge to investigate cathode sheath dynamics for the selective extraction of species 27−30 . In a nitrogen dc glow discharge the active species observed using optical emission spectroscopy (OES) are N (742, 744, and 746 nm) 27,30 , N 2 (316,337,357,380, and 405 nm) 27,28 , N + 2 (391, 421,470, and 522 nm) 27,29 . N + 2 ions are the most dominant species, and on entering the cathode sheath, they accelerate towards the negatively biased electrodes (say, the cathode voltage −V 0 ).…”
Section: Methods: Generation and Extraction Of Energetic N2mentioning
confidence: 99%
“…Tulane virus (1.08 ± 0.15 log CFU/cube), indigenous mesophilic bacteria (0.70 ± 0.12 log CFU/cube), and Salmonella (1.45 ± 0.05 log CFU/cube) from chicken samples were significantly reduced upon CP treatment (24 kV for 3 min), where increasing voltage (from 22 to 24 kV) and treatment time had a positive impact on the microbiological quality (123). However, the majority of cells showed morphological changes (cell flattened and other distortions) at 2,000 Hz, whereas at 1,000 Hz, only cell clumps appeared, and other cells were hollowed out (124). S. typhimurium, E. coli O157: H7, and L. monocytogenes populations on chicken breast reduced from 5.48, 5.84, and 5.88 log CFU/g, respectively, at 0 min to 2.77, 3.11, and 3.74 log CFU/g at 10-min plasma exposure (120).…”
Section: Effect Of Cold Plasma On Microbial Decontamination Of Poultry Productsmentioning
confidence: 99%
“…Other studies highlight the potential of in-package dielectric barrier discharge (DBD) (70 kV) in controlling poultry-related pathogens, namely, Salmonella and Campylobacter, and inhibiting the growth of spoiling bacteria (psychrophiles) from chicken breast treated and stored (5 days/4 • C) (23), where increasing CP treatment time to beyond 60 s improved microbial reduction of psychrophiles, while no significant effect was seen against foodborne pathogens. The in situ decontamination potential of plasma-activated water (PAW) against P. fluorescens ATCC13525 previously inoculated on chicken skin pieces was associated with the plasma process parameters of plasma discharge frequency and treatment time (124), where the concentration of plasma-generated reactive species of nitrite, nitrate, peroxide, hydroxyl, and ozone increased with the discharge frequency (124).…”
Section: Effect Of Cold Plasma On Microbial Decontamination Of Poultry Productsmentioning
confidence: 99%